Universal type/subtype-specific antibodies for quantitative analyses of neuraminidase in trivalent influenza vaccines - Kangwei Xu (Nature Portfolio, 2018)
Abstract Both influenza viral hemagglutinin and neuraminidase can induce protective immune responses in humans. Although the viral hemagglutinin antigens have been quantified in influenza vaccines, the amounts of neuraminidase remain undetermined. Using comprehensive bioinformatics analyses of all neuraminidase sequences, we identified highly conserved and subtype-specific peptide epitopes within each of N1, N2 and type B neuraminidase groups. Mono-specific antibodies generated against these peptides bound to their respective subtype/type only while demonstrating remarkable specificity against the viral neuraminidase sequences without any cross-reactivity with allantoic and cellular proteins. Moreover, the subtype/type-specific antibodies were found not to interfere with one another when a mixture of vaccine samples was analysed. Importantly, immunoassay based on these antibodies can quantitatively determine neuraminidase in commercial trivalent vaccine samples. Analyses of vaccines from eight manufacturers using the same vaccine seeds revealed significant differences in neuraminidase levels. Specifically, while the ratio between neuraminidase and hemagglutinin in some products are found to be close 1/5, other products have a ratio of approximately 1/100, a level which is far below the theoretical ratio between neuraminidase and hemagglutinin in a virus. The antibody-based assays reported here could be of great value for better quality control of both monovalent and trivalent vaccines.